Service Quality, Brand Trust, and Customer Retention: The ‎Competitive Dynamics between The Highway Food Chains and ‎Local Dhabas in India - Dev Varma, Hridayama; Kumar, Dr S Senthil (International Journal of Accounting and Economics Studies, 2025)
This study investigates the interplay between service quality, brand trust, and customer retention within retail food ‎chains operating along India’s national highways, with a particular focus on competition from local vendors ‎‎(dhabas). Drawing on the SERVQUAL model, the research examines six key constructs: service quality (across five ‎dimensions), restaurant atmosphere, customer relationship management (CRM), customer satisfaction, customer ‎loyalty, and brand trust. Data were collected from 409 customers, and 384 samples were used using structured ‎questionnaires at both branded outlets and dhabas, employing purposive sampling, and analyzed using SPSS. The ‎findings reveal that local dhabas, through lower pricing, faster service, and cultural familiarity, significantly erode ‎customer loyalty towards branded chains. Inconsistent experiences at branded outlets-such as poor hygiene, ‎substandard food quality, and unprofessional staff-were found to severely undermine both brand trust and loyalty. ‎Statistical analyses demonstrate that while direct effects of customer experience on loyalty are limited, their indirect ‎effects via customer satisfaction and, most notably, brand trust are substantial. Brand trust emerged as a stronger ‎mediator than customer satisfaction in the relationship between customer experience and loyalty.‎ The study underscores the critical need for highway food chains to ensure consistency in service delivery and to ‎strategically address the unique value propositions of local competitors. Insights from this research inform ‎actionable strategies for retail food chains aiming to enhance customer retention and competitive positioning in the ‎dynamic highway food service landscape‎.